Incidencia del precio de comercialización del barril de petróleo ecuatoriano en el endeudamiento público externo en el período 2013-2016 - Rodríguez Rodríguez, Beiggitte Estefanía (2018)
This research is to perform an analysis on the incidence of trading price of barrel of oil in the Ecuadorian external debt during the period 2013-2016, relying on investigative techniques in order to analyze the impact or involvement that had the Ecuadorian economy with price volatility of oil that was generated in this period. With gathering information is to provide a comprehensive analysis as the outcome that caused the low price of a barrel of oil relative to the country's debt in an economy that has depended on public spending, this event was a heavy blow to the state. The primary objective of this project is tonalize the incidence barrel price of Ecuadorian oil in the external public debt of the country, and establish theorie……..